Ultrasonic goniometric immersion tests for the characterization of fatigue post-LVI damage induced anisotropy superimposed to the constitutive anisotropy of polymer composites. (1st May 2017) - Castellano, Anna; Fraddosio, Aguinaldo; Piccioni, Mario Daniele
Abstract: We study an ultrasonic experimental approach for the damage characterization of polymer composites. Our approach is based on the key concept that damage of polymer composites involves a damage induced anisotropy superimposed to the constitutive anisotropy of the material. Thus, we correlate the damage to the analysis of the change in the anisotropy of the acoustic response of the material, by using an innovative goniometric ultrasonic immersion device designed and built at our laboratory. The experiments are performed on a glass fiber–reinforced composite material (GFRP), damaged first by a low velocity impact (LVI), and then by fatigue load cycles. We first identify possible changes in symmetry axes (acoustic axes) and/or in the symmetry class of the material due to the damage; to this aim, we compare the velocity curves and the slowness curves of the composite before and after the damage. Then, starting from the velocity measurements acquired in goniometric ultrasonic immersion tests performed before and after the damage, we determine the variations of the elastic constants due to the damage. For a quantitative characterization of the damage, a suitable anisotropic damage model developed in the framework of the Continuum Damage Mechanics theory is employed. In this model, the damage is related to the relative variation of the elastic constants of the material. For the validation of the procedure, ultrasonic results are also compared with experimental data obtained by conventional mechanical tests. The obtained results show the effectiveness of the proposed approach for the damage characterization of polymer composites.